The Correlation Between Students’ Habit of Watching English Movie and Their Vocabulary Mastery - Nurhayati, Nurhayati; Mamesah, Abellita G; Sanger, Alan H. F; Lasut, Elizabeth M. M (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study is to find out the correlation between students’ habit of watching English movie and their vocabulary mastery and used quantitative research. This study's respondents are 9th-grade students at SMP Advent Unklab Airmadidi, particularly those enrolled in the second semester of the academic year 2022/2023. This study is a descriptive and correlative design. The data was collected from 59 students from 9th grade of SMP Advent Unklab Airmadidi. Descriptive mean analysis and Pearson Product Coefficient Correlation were used to answer the research questions. The findings revealed that (1) the level of students’ habit of watching English movie was 4.30, indicating an often level; (2) the level of students’ vocabulary mastery was 4.29, indicating a high level; and (3) the p = 0.003 and r = 0.379, indicating that there is a significant correlation between students’ habit of watching English movie and their vocabulary mastery. And from the results show that there is a significant correlation between the two variables, and it is important for teachers to know that watching English movies is a good medium for students to learn English, especially for students’ vocabulary mastery.